2018
DOI: 10.21276/ijcmr.2018.5.10.21
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Serum Magnesium Level in Patients with Chronic Renal Failure at Tertiary Care Hospital

Abstract: Introduction: CKD represents a progressive irreversible decline in the glomerular filtration rate (GFR). A common phenomenon in renal failure is progressive renal function loss irrespective of the underlying cause of the kidney disease. Hypermagnesaemia is often associated with undetected renal impairment and excessive oral administration of magnesium containing drugs (e.g. laxatives or antacids) or with advanced CKD. The present study was conducted to assess serum magnesium levels in cases with chronic renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…These findings agreed with [11; 17; 18] who recorded that the Ca ++ showed significant decrease in HD patients, while phosphorus and K were increased in HD patients compared to control. These results no correspond with [6] who found that the mean Na + was increased, while mean of phosphorus, Mg and potassium were decreased in HD patients compared with control.…”
Section: Determination Of Serum Na Ca ++ P K and Mg ++ Among Four Study Groupscontrasting
confidence: 85%
See 1 more Smart Citation
“…These findings agreed with [11; 17; 18] who recorded that the Ca ++ showed significant decrease in HD patients, while phosphorus and K were increased in HD patients compared to control. These results no correspond with [6] who found that the mean Na + was increased, while mean of phosphorus, Mg and potassium were decreased in HD patients compared with control.…”
Section: Determination Of Serum Na Ca ++ P K and Mg ++ Among Four Study Groupscontrasting
confidence: 85%
“…The tissue sodium accumulation has different pathophysiologic that may be amenable to therapeutic strategies in CKD patients. While low serum magnesium levels are associated with vascular calcification and increased cardiovascular mortality in CKD patients [6] . Aims of the study to measure and compare the levels of urea, creatinine, albumin, and GFR in study groups and to assess serum electrolytes levels in HD patients and T2DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…[32]. NADPH is an important redox cofactor for metabolic processes, including fatty acid biosynthesis, and therefore increased synthesis of triglycerides and low density lipoproteins, and hence greater accumulation of triglycerides in adipocytes which increases the extent of obesity and the risk of obesity Morbidity such as dyslipidemia, metabolic syndrome and type 2 diabetes [33,34] and in a study that indicated that the high concentration of triglycerides is linked to insulin resistance through the entry of free fatty acids into the liver and thus increase the storage of fat in adipose tissue, which leads to obesity [35,36] On the other hand, recent studies have linked magnesium with kidney patients [37] and polycystic ovary syndrome [38] and hypothyroidism patients [39]. The proportion of magnesium in women was lower than in men in obesity and overweight, as studies conducted on groups showed Different populations show that 15-42% of ostensibly healthy adults have abnormal serum Mg levels.…”
Section: Discussionmentioning
confidence: 99%